ANALISIS PERUBAHAN PENGGUNAAN LAHAN DAN KETERSEDIAAN SUMBERDAYA AIR DI DAS KONAWEHA PROPINSI SULAWESI TENGGARA - MARWAH, SITTI (Jurnal Agroteknos, 2014)
Phenomena of depleting of water resources and increasing water demand have been occurring in Konaweha watershed. Combine with other degraded conditions, Konaweha watershed have been categorized as priority watershed in Southeast Sulawesi Province. Land use change is the main factor to influence water balance that indicated by the increasing maximum discharge in rainy seasons and decreasing minimum discharge in dry seasons. The objective of this research were (1) to analize the effects of land use changes onwater resources of Konaweha watershed; (2) to analize the availability of water resources to meet water demand as well as minimum proportion of forest cover in the watershed to ensure sustainable water resources in Konaweha watershed. This research was conducted in Konaweha watershed for 7 months from July 2011 to February 2012.  The result of this research showed that forest, swamp, plantation and bush area tended to decline exponentially year by year. The decline of forest area have significantly decreased minimum discharge of Konaweha River in dry seasons and increased maximum discharge in rainy seasons.  These condition have caused a significant deficit of water resources in dry seasons since period of 2004 to 2010 eventhough there was no deficit of annual water resources.